COMPENSATION, WORK DISCIPLINE, AND EMPLOYEE PERFORMANCE: EXAMINING THE MEDIATING ROLE OF WORK MOTIVATION IN THE PUBLIC JUDICIARY SECTOR - Dwi Raharjo; H. Fajar Supanto; Estikowati (Adisam Publisher, 2026)
This study investigates the effect of compensation and work discipline on employee performance, with work motivation serving as a mediating variable, in the context of a public judicial institution. Employee performance in the public sector plays a critical role in ensuring service quality, institutional accountability, and the effective implementation of good governance principles. However, empirical evidence focusing on judicial institutions remains limited. This research adopts a quantitative approach using a survey method. Data were collected from civil servants employed at the Bangil District Court, Indonesia, through structured questionnaires. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The findings indicate that compensation and work discipline have a positive and significant effect on work motivation. Furthermore, compensation, work discipline, and work motivation each have a direct and significant impact on employee performance. The mediation analysis reveals that work motivation partially mediates the relationship between compensation and employee performance, as well as between work discipline and employee performance. These results confirm that motivation serves as a critical psychological mechanism through which organizational practices influence performance outcomes. This study contributes to the literature on human resource management in the public sector by providing empirical evidence from the judicial environment, which has been relatively underexplored. Practically, the findings suggest that judicial institutions should strengthen fair compensation systems and consistently enforce work discipline to enhance employee motivation and performance.